Improving Service Quality that Affects Tourists’ Revisit Intention in the Digital Age: A Case Study of the Rajamangala University of Technology Trang Aquarium - Rattanaaramsawat, Witsanee (Journal of Public Administration Chiang Rai Rajabhat University, 2025)
This research aims to (1) examine the level of service quality development that influences tourists’ revisit intention in the digital era, using Rajamangala Trang Aquarium as a case study, and (2) investigate the factors in service quality development that affect tourists’ revisit intention. The study sample comprised 400 Thai tourists who visited the Rajamangala Trang Aquarium. Data collection was conducted using a structured questionnaire, which was validated for content validity through an Index of Item-Objective Congruence (IOC), with values ranging from 0.67 to 1.00, and for reliability using Cronbach’s Alpha, yielding an overall reliability coefficient of 0.950. Data analysis was performed using descriptive statistics and inferential statistics, employing a stepwise multiple regression analysis. The findings reveal that (1) the overall level of service quality development influencing revisit intention in the digital era was rated at the highest level, and (2) the development of service quality in terms of online experience, offline experience, psychological and social factors, and integrated experiential engagement positively influenced tourists’ revisit intention. Among these, offline experience had the most significant impact, while the integration of digital and offline experiences played a crucial role in enhancing convenience and fostering tourists’ emotional connection with the aquarium, ultimately strengthening their intention to revisit in the future. This study offers practical recommendations, including developing digital platforms for promotion, organizing interactive online activities, and training staff in technological competencies, which can be applied in service strategy planning to effectively enhance visitor engagement and revisit intention.